Answer:
x1 = - 4
x2 = 2/3
Explanation:
Divide the equation by 3 to give
x^2 + 10x/3 + c/3 = 0
The sum of the two roots = - 10/3
So
x1 + x2 = -10/3
x1 - x2 = 4 2/3 Add these two equations.
2x1 = -10/3 + 4 2/3 Change 4 2/3 to an improper fraction
2x1 = -10/3 + 14/3 Combine the right
2x1 = 4/3 Divide by 2
2x1/2 =4/3//2
x1 = 2/3
=====================
x1 + x2 = - 10/3
2/3 + x2 = - 10/3
x2 = - 10/3 - 2/3
x2= -12/3
x2 = - 4
=================
(x - 2/3)(x +4) = 0 Multiply through by 3
(3x - 2)(x + 4) =0
==============
Check
(3x - 2)(x + 4) = 0
3x^2 + 12x - 2x - 8 =0
3x^2 + 10x - 8 = 0